Preparation method of degradable oil-proof paper
By combining materials such as nanocellulose, bagasse pulp, and modified starch, a porous substrate layer and a gradient sandwich structure are constructed, which solves the contradiction between the oil-proof performance and biodegradability of greaseproof paper. This results in high-performance, low-cost biodegradable greaseproof paper with intelligent degradation and antibacterial functions, making it suitable for high-end packaging materials.
Patent Information
- Application Number
- CN202511531724.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-24
- Publication Date
- 2025-12-16
AI Technical Summary
Existing greaseproof paper suffers from several drawbacks, including a negative correlation between greaseproof performance and biodegradability, high cost, limited functionality, poor moisture resistance, lack of intelligent response and antibacterial properties, and uncontrollable degradation rate, making it difficult to meet the needs of high-end applications.
A porous base layer is formed by mixing nanocellulose, sugarcane bagasse pulp and modified starch. A hydrophilic barrier layer is formed by spraying sodium alginate-chitosan composite solution. An anthocyanin microcapsules, zein and hydrophobically modified nano silica are coated to form an oil-resistant layer. The combination of gradient sandwich structure and integrated coating process achieves oil-resistant, breathable, moisture-resistant and antibacterial functions.
It achieves an oil resistance rating of ≥9 and a natural degradation rate of ≥90% in 90 days. It features intelligent degradation visualization, mechanical stability and broad-spectrum antibacterial properties in high humidity environments, and the degradation process is visualized, making it suitable for high-end packaging materials.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of functional packaging materials technology, specifically to a biodegradable oil-resistant paper and its preparation method. Background Technology
[0002] Traditional greaseproof paper primarily uses fluorocarbon coatings such as perfluorooctanoic acid (PFOA) and perfluorooctane sulfonic acid (PFOS) or polyethylene plastic lamination technology. The CF bond energy of fluorocarbons is as high as 485 kJ / mol, making them extremely difficult to break in the natural environment. Their half-lives can reach decades, posing an ecological threat through bioaccumulation in the food chain. While plastic lamination is cheaper, it faces challenges in microplastic pollution and waste disposal. Fluorocarbon coatings achieve grease resistance based on ultra-low surface energy, but their chemical inertness is the root cause of their environmental persistence. Plastic lamination blocks oils through a continuous hydrophobic barrier, but its impermeability affects the quality of packaged food, and pyrolysis produces toxic gases.
[0003] Existing bio-based oil-repellent materials face a core contradiction: a negative correlation between oil-repellent performance and biodegradability. Polylactic acid (PLA) provides barrier properties by forming a dense network through ester crosslinking, but these hydrophilic ester bonds are easily hydrolyzed by microbial enzymes, leading to a rapid decline in oil-repellent performance. While starch-based materials possess excellent degradability, the large number of hydroxyl groups in their molecular chains makes them highly hydrophilic, lacking effective oil repellency. To enhance oil repellency, chemical crosslinking and surface modification are commonly used to improve density and hydrophobicity; however, these modifications reduce molecular chain flexibility and the accessibility of enzymatic hydrolytic sites, slowing down the degradation process. Acetylation of starch improves hydrophobicity but hinders amylase recognition, thus decreasing the degradation rate.
[0004] Existing bio-based oleophobic paper heavily relies on wood pulp fibers, consuming vast amounts of forest resources, and generating secondary pollution such as chlorinated organic compounds during the pulping process. The unevenness of wood pulp fibers affects product quality stability. Multi-layer coating processes require multiple steps, including primer, topcoat, drying, and calendering, with each layer requiring independent drying, resulting in enormous energy consumption. The coating solution requires precise control of solid content, viscosity, and pH, placing extremely high demands on equipment and processes. Insufficient interlayer bonding in multi-layer structures can easily lead to delamination, affecting performance.
[0005] Existing bio-based greaseproof paper has limited functionality, primarily focusing on basic grease barrier properties, lacking extended functions such as moisture resistance, antibacterial properties, and intelligent response. In high humidity environments, moisture absorption and expansion damage the coating integrity, causing a sharp decline in greaseproof performance. Furthermore, the lack of antibacterial mechanisms makes it susceptible to microbial growth during storage and use.
[0006] Uncontrollable degradation progress is a significant obstacle, as it is affected by multiple factors such as temperature, humidity, and pH, making precise time control difficult. The lack of effective degradation monitoring methods prevents users from determining the remaining lifespan. The absence of intelligent features also limits the adoption of advanced applications such as temperature indication and freshness detection. Summary of the Invention
[0007] This invention addresses the technical challenges of traditional paper, such as performance inconsistencies, high cost, and limited functionality, by providing a biodegradable oil-proof paper and its preparation method.
[0008] The main objective of this invention is to: 1. overcome the contradiction between "oil resistance and degradation" performance, and achieve an oil resistance level of ≥9 and a natural degradation rate of ≥90% in 90 days.
[0009] Second, reduce costs through material and structural innovation.
[0010] Third, it integrates intelligent degradation visualization and moisture-resistant antibacterial functions, making it suitable for high-humidity environments.
[0011] To achieve the above objectives, the present invention adopts the following technical solution.
[0012] A method for preparing biodegradable greaseproof paper, the method comprising: 1) mixing nanocellulose, sugarcane bagasse pulp and modified starch, and forming a porous substrate layer by wet papermaking.
[0013] 2) Spray a sodium alginate-chitosan composite solution onto the surface of the substrate to form a hydrophilic barrier layer.
[0014] 3) Anthocyanin microcapsules, zein and hydrophobically modified nano-silica are blended into a coating material and coated on the surface of the barrier layer to form an oil-proof layer, thus making a biodegradable oil-proof paper.
[0015] Preferably, the nanocellulose in step 1) is microfibrillated cellulose with a fiber length of 1.2 to 1.5 mm, and its addition amount is 38 to 42% of the total mass of the mixed slurry.
[0016] Step 1) The bagasse pulp is bleached bagasse pulp that has undergone delignification treatment.
[0017] Step 1) The modified starch is hydroxypropylated cassava starch, and its addition amount is 8-12% of the total mass of the mixed slurry.
[0018] Preferably, the wet papermaking process in step 1) is carried out at a water temperature of 43–47 °C, a slurry concentration of 0.8–1.2 wt%, and a papermaking pressure of 0.1 MPa, resulting in a substrate layer thickness of 0.12–0.15 mm and a porosity of 60–70%.
[0019] Preferably, the sodium alginate-chitosan composite solution in step 2) consists of 2-3 wt% sodium alginate, 1.5-2.5 wt% chitosan, 0.5-1 wt% citric acid, and the remainder being distilled water.
[0020] Preferably, the spraying amount of the sodium alginate-chitosan composite solution in step 2) is 6–10 g / m². 2The substrate is uniformly sprayed with an air knife coating machine and dried with hot air at 38-42 ℃ for 30-50 s.
[0021] Preferably, the anthocyanin microcapsules in step 3) have a particle size of 50–80 μm and are added at 6–8% of the total mass of the coating material.
[0022] Step 3) The zein is a zein ethanol solution with a zein content of 10-15 wt%.
[0023] Step 3) The hydrophobic modified nano-silica particles have a particle size of 80-100 nm and are added at 15-20% of the total mass of the coating.
[0024] As a preferred embodiment, the anthocyanin microcapsules in step 3) are prepared as follows: anthocyanin solution and wall material solution are prepared separately, and anthocyanin microcapsules are prepared by sharp-pore coagulation bath method.
[0025] As a preferred embodiment, the modification method of the hydrophobic modified nano silica in step 3) is as follows: nano silica and octadecyltrimethoxysilane are mixed evenly at a mass ratio of 1:0.2 and reacted at an ambient temperature of 75 °C for 2 h.
[0026] Preferably, the coating process in step 3) employs a microgravure coating method, with the coating amount controlled at 5–7 g / m². 2 After coating, pre-curing at 58–62 °C for 5–7 min, followed by curing at 79–81 °C for 2–4 min, results in an oil-resistant layer thickness of 0.03–0.05 mm.
[0027] A biodegradable oil-resistant paper.
[0028] The core of this invention lies in the systematic innovation of material combination, structural design, process optimization and intelligent functions to build a high-performance bio-based oleophobic paper technology platform, thereby achieving a synergistic unity of oleophobic performance, environmental friendliness and intelligent functions.
[0029] In this invention, a multi-component synergistic mechanism is employed to construct a microfibrillated cellulose-bagasse pulp composite substrate. Microfibrillated cellulose possesses a high aspect ratio and excellent mechanical properties; its nanoscale diameter and micrometer-scale length form a high-density fiber network, providing superior tensile and tear strength through inter-fiber hydrogen bonding. Bagasse pulp, as an agricultural waste, not only reduces raw material costs, but its short fiber structure also fills the gaps in the microfibrillated cellulose network, optimizing pore distribution. The high surface hydroxyl density of microfibrillated cellulose forms numerous intermolecular hydrogen bonds with bagasse pulp fibers, constructing a stable three-dimensional network structure. This composite substrate, while maintaining biodegradability, significantly improves wet strength and dimensional stability, providing an ideal carrier platform for subsequent functional layer coating.
[0030] In this invention, the hydrophobicity of zein originates from its unique molecular structure, containing a large number of hydrophobic amino acid residues that spontaneously form a β-sheet secondary structure in aqueous solution. The silanol groups on the surface of nano-silica are methylated to form hydrophobic groups, which bind to the hydrophobic regions of the zein protein through hydrophobic interactions. This protein-inorganic nanoparticle composite system forms a dense oil-resistant network, and its oil-resistant mechanism is based on a dual barrier effect: the zein protein matrix provides a continuous phase, preventing the large-scale diffusion of oil molecules; the nano-silica, as a dispersed phase, forms complex diffusion channels in the protein matrix, extending the penetration path of oil molecules and forming an effective oleophobic surface, significantly improving the oil permeation resistance.
[0031] This invention employs a sodium alginate-chitosan electrostatic self-assembled barrier layer. Under suitable pH conditions, the carboxyl groups of sodium alginate and the amino groups of chitosan undergo electrostatic interactions to form a polyelectrolyte complex. This electrostatic self-assembly process is spontaneous and reversible, enabling the formation of a dense barrier layer at the interface. The unique feature of the polyelectrolyte complex structure lies in its humidity-responsive characteristics. In low-humidity environments, electrostatic interactions dominate, resulting in a tight ion-pair structure. In high-humidity environments, the insertion of water molecules partially shields the electrostatic interactions, but the formation of a hydrogen bond network compensates for the loss of binding force. This dynamic equilibrium mechanism allows the barrier layer to maintain structural integrity under different humidity conditions, exhibiting a high wet strength retention rate.
[0032] Furthermore, this invention constructs a gradient sandwich structure that achieves a balance between breathability and barrier properties through precise pore size distribution. The large pore size of the base layer ensures the free diffusion of gas molecules, meeting the breathability requirements of packaging materials; the medium pore size of the barrier layer allows gas to pass through but prevents the penetration of liquid water; and the microporous structure of the oil-resistant layer forms an effective barrier against oil molecules. This gradient pore design is based on molecular dynamics theory. The diffusion behavior of molecules of different sizes in porous media varies significantly. Gas molecules have a smaller dynamic diameter and can diffuse freely across all pore sizes; water molecules, due to their strong polarity and hydrogen bonding, have their diffusion hindered in hydrophobic micropores; and the diffusion of oil molecules in the microporous structure is severely restricted. Simultaneously, this invention, by adjusting the cross-linking degree of zein protein and the dispersion uniformity of nano-silica, forms a defect-free continuous coating, ensuring sufficient oil resistance while avoiding the decrease in flexibility caused by excessively thick coatings.
[0033] This invention employs an integrated coating and molding technology using a tandem coating machine, continuously completing the application of the barrier layer and the oil-resistant layer on the same production line. The core of this process innovation lies in the control of the interfacial compatibility and the matching of curing kinetics between the two coating liquids. When the barrier layer coating liquid (sodium alginate-chitosan system) and the oil-resistant layer coating liquid (zein-silica system) come into contact in a wet state, intermolecular interactions occur at the interface. The carboxyl groups of sodium alginate form hydrogen bonds with the amino groups of zein, and the amino groups of chitosan electrostatically adsorb onto the silanol groups on the silica surface. These interfacial interactions enhance the interlayer bonding force and prevent delamination. In traditional step-by-step drying processes, each coating layer requires an independent drying process, resulting in significant energy consumption. The integrated process achieves synergistic drying of the two layers by optimizing the drying temperature gradient and time control. The initial low temperature mainly removes surface moisture, avoids skin formation on the coating surface, and promotes internal moisture diffusion. The subsequent high temperature completes the final curing. This gradient drying process improves the microstructure of the coating. The slow moisture removal process is conducive to the orderly arrangement of molecular chains and the formation of hydrogen bond networks, thereby improving the density and mechanical properties of the coating.
[0034] Another key aspect of this invention is the use of anthocyanin microcapsules to achieve a pH-responsive color-changing mechanism. The microcapsules are specifically embedded within the oil-resistant layer, avoiding distribution in the base layer and barrier layer, thus preventing color changes during processing. The key to this precise embedding lies in controlling the compatibility between the microcapsules and the oil-resistant layer matrix. By adjusting the hydrophilicity and hydrophobicity of the microcapsule surface, they are preferentially dispersed in the zein protein phase, rather than agglomerating in the aqueous phase or at the interface. This selective distribution ensures the precise positioning and long-term stability of the color-changing function.
[0035] The pH-responsive color-changing mechanism of anthocyanins is based on the protonation-deprotonation equilibrium of their molecular structure. Under acidic conditions, anthocyanins exist as flavonoid cations, exhibiting a reddish-purple color. As the pH increases, the molecules undergo deprotonation and structural rearrangement, gradually changing color to blue, then green, and finally yellow under strongly alkaline conditions. In composting environments, ammonia compounds produced by microbial metabolism gradually increase the local pH, triggering the color change of anthocyanins. This color-changing process is highly correlated with the biodegradation process of the material: in the early stages of degradation, the color changes from purple to blue; in the middle stages, it changes from blue to green; and in the later stages, it changes from green to yellow, enabling intuitive and visual monitoring of the degradation progress.
[0036] The advantages of this invention are: it provides a low-cost, high-performance bio-based raw material base through material combination, supporting the construction and functional realization of gradient structures; the structural design achieves a precise balance of oil resistance, breathability, and moisture resistance through a multi-level architecture; the process ensures efficient manufacturing of complex structures and complete preservation of microcapsule functions; and it endows materials with environmental responsiveness and self-monitoring capabilities. Detailed Implementation
[0037] The present invention will be further described clearly and in detail below with reference to specific embodiments. Those skilled in the art will be able to implement the present invention based on these descriptions. Furthermore, the embodiments of the present invention described below are generally only some, not all, of the embodiments of the present invention. Therefore, all other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort should fall within the scope of protection of the present invention.
[0038] Unless otherwise specified, all raw materials used in the embodiments of the present invention are commercially available or obtainable by those skilled in the art; unless otherwise specified, all methods used in the embodiments of the present invention are methods mastered by those skilled in the art.
[0039] Unless otherwise specified, the specific preparation method of the anthocyanin microcapsules used in the embodiments of the present invention is as follows: Industrial anthocyanins are dissolved in deionized water to prepare a 5 wt% anthocyanin solution. Gelatin and gum arabic are mixed at a mass ratio of 3:1 as a wall material and dissolved in deionized water at 50 ℃, stirred until transparent to prepare a wall material solution with a total wall material concentration of 5 wt%. The anthocyanin solution and the wall material solution are taken at a mass ratio of 1:3. 0.5 wt% of Tween 80 is added to the wall material solution. The wall material solution is preheated to 40 ℃ and continuously stirred at 300 rpm. The anthocyanin solution is slowly and uniformly added to the wall material solution over 30 min, and then stirred at 5000 rpm for 10 min for emulsification. Subsequently, a sharp-pore forming coagulation bath is used, with the sharp-pore parameters set as follows: pore diameter 0.5 mm, drop rate 20 mL / min, and coagulation bath solution 2.0 wt% calcium chloride aqueous solution with 0.1... The pH was slowly adjusted to 4.0 using a wt% acetic acid aqueous solution. The coagulation bath temperature was set to 25 ℃, the drop distance to 10 cm, and the solidification time to 40 min, with gentle stirring at 200 rpm. After the coagulation bath, the mixture was filtered, washed three times with deionized water, and then dried at a constant temperature of 40 ℃ to obtain anthocyanin microcapsules.
[0040] Unless otherwise specified, the specific modification method of the hydrophobically modified nano-silica used in the embodiments of the present invention is as follows: nano-silica and octadecyltrimethoxysilane are mixed evenly at a mass ratio of 1:0.2 and reacted at an environment temperature of 75 ℃ for 2 h to obtain the product.
[0041] Example 1: A method for preparing biodegradable greaseproof paper, the method comprising: 1) mixing microfibrillated cellulose with a fiber length of 1.2 mm, bleached bagasse pulp treated with delignification and hydroxypropylated cassava starch in the proportions shown in the table below, and performing wet papermaking under the conditions of water temperature of 43 ℃, pulp concentration of 0.8 wt% and papermaking pressure of 0.1 MPa to form a porous base layer with a thickness of 0.12 mm and a porosity of 60%.
[0042]
[0043] 2) Prepare a sodium alginate-chitosan composite solution by mixing 2 wt% sodium alginate, 1.5 wt% chitosan (90% deacetylation), 0.5 wt% citric acid, and the balance being distilled water. Apply the composite solution evenly to the substrate using an air knife coating machine at a single-sided coating rate of 6 g / m². 2 After being dried with hot air at 38 ℃ for 50 s, a hydrophilic barrier layer is formed.
[0044] 3) Anthocyanin microcapsules with a particle size of 50 μm, a food-grade zein ethanol solution with a zein content of 10 wt%, and hydrophobically modified nano-silica with a particle size of 80 nm were blended according to the proportions in the table below. The mixture was then applied using a microgravure coating method, with the coating amount controlled at 5 g / m². 2 After coating, the paper is pre-cured at 58 ℃ for 7 min, and then cured at 79 ℃ for 4 min. The resulting oil-proof layer has a thickness of 0.03 mm, and is made into biodegradable oil-proof paper.
[0045]
[0046] The materials prepared in the examples were subjected to performance testing, and the specific characterization results are as follows.
[0047] Oil resistance performance testing: Referring to GB / T 22805.2-2008 "Determination of Grease Resistance of Paper and Paperboard - Kit Test Method", the oil resistance effect of the material is evaluated using a standard ink penetration test. The test uses a standard ink prepared with castor oil, toluene, and heptane in a 1:1:1 volume ratio. 0.1 mL of the ink is dropped onto the paper surface, then covered with standard oil-permeable paper. A 5 kg weight is applied under static pressure for 30 min, and the number of stains on the oil-permeable paper is observed.
[0048] Degradation performance testing: Referring to ISO 14855-1:2012 "Aerobic biodegradation capacity under controlled composting conditions," the environmental friendliness of the material was assessed using the compost biodegradation method. The sample was shredded to 2×2 mm and mixed with compost at pH 8.0 and 55% moisture content at a C / N ratio of 20:1. The mixture was placed in a 60 ℃ compost reactor for 90 days, after which the carbon dioxide release was measured. The degradation rate was calculated as (measured carbon dioxide / theoretical carbon dioxide) × 100%.
[0049] Wet strength test: The wet strength test is conducted in accordance with GB / T 12914-2018 "Determination of tensile strength of paper and paperboard". The sample is placed in an environment of 38 ℃ and 95% relative humidity for 24 h and the longitudinal tensile strength is measured. The wet strength retention rate is calculated as (wet strength / dry strength) × 100%.
[0050] Air permeability test: The air permeability test was conducted in accordance with GB / T 458-2008 "Determination of air permeability of paper and paperboard - Gurley method".
[0051] Antimicrobial performance testing: The antimicrobial effect of the material was evaluated according to GB / T 31402-2015 "Test Method for Antimicrobial Properties of Plastic Surfaces". Escherichia coli and Staphylococcus aureus were used as representative Gram-negative and Gram-positive bacteria, respectively. After inoculating the sample surface with bacterial solutions, the samples were incubated at 37 ℃ for 144 h. The inhibition rate was calculated using the formula R = (BA) / B × 100%, where A is the number of colonies in the sample and B is the number of colonies in the control sample.
[0052]
[0053] Analysis of the above characterization results shows that the biodegradable oleophobic paper prepared in Example 1 exhibits excellent comprehensive performance. The number of oil-permeable stains is only 3, far below the industry standard requirement (usually ≤8), which fully confirms that the dense oleophobic network formed by the oleophobic layer (zein-hydrophobically modified nano-silica composite system) has an excellent oleophobic barrier effect. The degradation rate is as high as 94.2%, significantly better than conventional oleophobic paper. This is attributed to the fact that both the substrate (microfibrillated cellulose-bagasse pulp) and the functional layer (sodium alginate-chitosan, zein) are made from completely bio-based and biodegradable raw materials, ensuring the overall environmental friendliness of the material. The wet strength retention rate reaches 86.5%, indicating that even under harsh high humidity conditions (38 ℃, 95%RH), the material can still maintain excellent mechanical properties. This is mainly due to the combined effect of the high-density hydrogen bonding of the microfibrillated cellulose network in the substrate layer and the dynamic equilibrium mechanism of the barrier layer (sodium alginate-chitosan electrostatic self-assembly layer) under humidity changes. The air permeability is 12.2 s / 100mL, which is within a suitable range, proving that the gradient sandwich structure's pore size distribution design effectively balances air permeability and oil / moisture resistance. Particularly noteworthy is its antibacterial performance, with inhibition rates of 99.5% against Escherichia coli and 99.8% against Staphylococcus aureus. This is attributed to the inherent broad-spectrum antibacterial activity of chitosan and the synergistic effect of citric acid, endowing the material with excellent hygiene and safety properties.
[0054] Example 2: A method for preparing biodegradable greaseproof paper, the method comprising: 1) mixing microfibrillated cellulose with a fiber length of 1.4 mm, bleached bagasse pulp treated with delignification and hydroxypropylated tapioca starch in the proportions shown in the table below, and performing wet papermaking under the conditions of water temperature of 45 ℃, pulp concentration of 1 wt% and papermaking pressure of 0.1 MPa to form a porous base layer with a thickness of 0.14 mm and a porosity of 65%.
[0055]
[0056] 2) Prepare a sodium alginate-chitosan composite solution by mixing 2.5 wt% sodium alginate, 2 wt% chitosan (90% deacetylation), 0.75 wt% citric acid, and the balance being distilled water. Apply the composite solution evenly to the substrate using an air knife coating machine at a single-sided coating rate of 8 g / m². 2 After being dried with hot air at 40 ℃ for 40 s, a hydrophilic barrier layer is formed.
[0057] 3) Anthocyanin microcapsules with a particle size of 65 μm, a food-grade zein ethanol solution with a zein content of 13 wt%, and hydrophobically modified nano-silica with a particle size of 90 nm were blended according to the proportions in the table below. The mixture was then applied using a microgravure coating method, with the coating amount controlled at 6 g / m². 2 After coating, the paper is pre-cured at 60 °C for 6 min, and then cured at 80 °C for 3 min. The resulting oil-proof layer has a thickness of 0.04 mm, and is made into a biodegradable oil-proof paper.
[0058]
[0059] The materials prepared in the examples were subjected to performance testing, and the specific characterization results are as follows.
[0060] Oil resistance performance testing: Referring to GB / T 22805.2-2008 "Determination of Grease Resistance of Paper and Paperboard - Kit Test Method", the oil resistance effect of the material is evaluated using a standard ink penetration test. The test uses a standard ink prepared with castor oil, toluene, and heptane in a 1:1:1 volume ratio. 0.1 mL of the ink is dropped onto the paper surface, then covered with standard oil-permeable paper. A 5 kg weight is applied under static pressure for 30 min, and the number of stains on the oil-permeable paper is observed.
[0061] Degradation performance testing: Referring to ISO 14855-1:2012 "Aerobic biodegradation capacity under controlled composting conditions," the environmental friendliness of the material was assessed using the compost biodegradation method. The sample was shredded to 2×2 mm and mixed with compost at pH 8.0 and 55% moisture content at a C / N ratio of 20:1. The mixture was placed in a 60 ℃ compost reactor for 90 days, after which the carbon dioxide release was measured. The degradation rate was calculated as (measured carbon dioxide / theoretical carbon dioxide) × 100%.
[0062] Wet strength test: The wet strength test is conducted in accordance with GB / T 12914-2018 "Determination of tensile strength of paper and paperboard". The sample is placed in an environment of 38 ℃ and 95% relative humidity for 24 h and the longitudinal tensile strength is measured. The wet strength retention rate is calculated as (wet strength / dry strength) × 100%.
[0063] Air permeability test: The air permeability test was conducted in accordance with GB / T 458-2008 "Determination of air permeability of paper and paperboard - Gurley method".
[0064] Antimicrobial performance testing: The antimicrobial effect of the material was evaluated according to GB / T 31402-2015 "Test Method for Antimicrobial Properties of Plastic Surfaces". Escherichia coli and Staphylococcus aureus were used as representative Gram-negative and Gram-positive bacteria, respectively. After inoculating the sample surface with bacterial solutions, the samples were incubated at 37 ℃ for 144 h. The inhibition rate was calculated using the formula R = (BA) / B × 100%, where A is the number of colonies in the sample and B is the number of colonies in the control sample.
[0065]
[0066] Analysis of the characterization results shows that the biodegradable oleophobic paper prepared in Example 2 also exhibits excellent overall performance, with some indicators showing improvement over Example 1. The number of oil-permeable paper stains is as low as 2, further confirming the synergistic effect of the oleophobic layer (zein-hydrophobically modified nano-silica composite system) under high proportion of hydrophobic nanoparticles and optimized coating process, forming a denser and more oleophobic barrier network. The degradation rate is as high as 94.7%, slightly better than Example 1. This is attributed to the increased proportion of microfibrillated cellulose in the base layer and the completely bio-based nature of the functional layer raw materials, ensuring efficient and complete degradation of the material in a composting environment. The wet strength retention rate reaches 88.9%, indicating further enhanced mechanical stability of the material under high humidity conditions. This is mainly attributed to the denser hydrogen bond network formed by the higher content of microfibrillated cellulose in the base layer, and the stronger wet bonding force resulting from the increased coating amount of the barrier layer (sodium alginate-chitosan). The air permeability was 12.0 s / 100mL, comparable to Example 1, remaining within a suitable range. This demonstrates that even with a slight increase in substrate thickness and porosity, the gradient structure design effectively balances air permeability and barrier properties. The antibacterial properties were also exceptionally good, with inhibition rates of 99.6% and 99.8% against Escherichia coli and Staphylococcus aureus, respectively. This was mainly due to the increased concentrations of chitosan and citric acid in the barrier layer, significantly enhancing the material's broad-spectrum antibacterial activity.
[0067] Example 3: A method for preparing biodegradable greaseproof paper, the method comprising: 1) mixing microfibrillated cellulose with a fiber length of 1.5 mm, bleached bagasse pulp treated with delignification, and hydroxypropylated cassava starch in the proportions shown in the table below, and performing wet papermaking under the conditions of water temperature of 47 ℃, pulp concentration of 1.2 wt%, and papermaking pressure of 0.1 MPa to form a porous base layer with a thickness of 0.15 mm and a porosity of 70%.
[0068]
[0069] 2) Prepare a sodium alginate-chitosan composite solution by mixing sodium alginate (3 wt%), chitosan (90% deacetylation), citric acid (1 wt%), and the balance being distilled water. Apply the composite solution evenly to the substrate using an air knife coating machine at a single-sided coating rate of 10 g / m². 2 After being dried with hot air at 42 ℃ for 30 s, a hydrophilic barrier layer is formed.
[0070] 3) Anthocyanin microcapsules with a particle size of 80 μm, a food-grade zein ethanol solution with a zein content of 15 wt%, and hydrophobically modified nano-silica with a particle size of 100 nm were blended according to the proportions in the table below. The mixture was then applied using a microgravure coating method, with the coating amount controlled at 7 g / m². 2 After coating, the paper is pre-cured at 62 °C for 5 min, and then cured at 81 °C for 2 min. The resulting oil-proof layer has a thickness of 0.05 mm, and is made into a biodegradable oil-proof paper.
[0071]
[0072] The materials prepared in the examples were subjected to performance testing, and the specific characterization results are as follows.
[0073] Oil resistance performance testing: Referring to GB / T 22805.2-2008 "Determination of Grease Resistance of Paper and Paperboard - Kit Test Method", the oil resistance effect of the material is evaluated using a standard ink penetration test. The test uses a standard ink prepared with castor oil, toluene, and heptane in a 1:1:1 volume ratio. 0.1 mL of the ink is dropped onto the paper surface, then covered with standard oil-permeable paper. A 5 kg weight is applied under static pressure for 30 min, and the number of stains on the oil-permeable paper is observed.
[0074] Degradation performance testing: Referring to ISO 14855-1:2012 "Aerobic biodegradation capacity under controlled composting conditions," the environmental friendliness of the material was assessed using the compost biodegradation method. The sample was shredded to 2×2 mm and mixed with compost at pH 8.0 and 55% moisture content at a C / N ratio of 20:1. The mixture was placed in a 60 ℃ compost reactor for 90 days, after which the carbon dioxide release was measured. The degradation rate was calculated as (measured carbon dioxide / theoretical carbon dioxide) × 100%.
[0075] Wet strength test: The wet strength test is conducted in accordance with GB / T 12914-2018 "Determination of tensile strength of paper and paperboard". The sample is placed in an environment of 38 ℃ and 95% relative humidity for 24 h and the longitudinal tensile strength is measured. The wet strength retention rate is calculated as (wet strength / dry strength) × 100%.
[0076] Air permeability test: The air permeability test was conducted in accordance with GB / T 458-2008 "Determination of air permeability of paper and paperboard - Gurley method".
[0077] Antimicrobial performance testing: The antimicrobial effect of the material was evaluated according to GB / T 31402-2015 "Test Method for Antimicrobial Properties of Plastic Surfaces". Escherichia coli and Staphylococcus aureus were used as representative Gram-negative and Gram-positive bacteria, respectively. After inoculating the sample surface with bacterial solutions, the samples were incubated at 37 ℃ for 144 h. The inhibition rate was calculated using the formula R = (BA) / B × 100%, where A is the number of colonies in the sample and B is the number of colonies in the control sample.
[0078]
[0079] Analysis of the characterization results shows that the biodegradable oleophobic paper prepared in Example 3 exhibits excellent comprehensive performance, with some indicators showing significant improvement under optimized parameters. The number of oil-permeable stains was 4, slightly higher than in Example 2, but still far below industry standard requirements. This indicates that the oleophobic layer (zein-hydrophobically modified nano-silica composite system) forms a highly dense oleophobic network under the synergistic effect of a high proportion of hydrophobic nano-silica and anthocyanin microcapsules, effectively resisting ink penetration. The degradation rate reached 95.0%, the highest among the three, thanks to the increased proportion of microfibrillated cellulose in the base layer (42 wt%) and the increased proportion of hydroxypropylated cassava starch, as well as the contribution of completely bio-based raw materials in the functional layer (sodium alginate-chitosan and zein system), ensuring efficient and near-complete biodegradation of the material in a composting environment. The wet strength retention rate reached 83.9%, indicating that the material's mechanical properties remained good under high humidity conditions (38 °C, 95% RH), despite the increased porosity of the base layer to 70%. This was mainly attributed to the high-density hydrogen bonding of the microfibrillated cellulose network and the enhanced wet stability resulting from the increased amount of barrier layer coating. The air permeability was 12.1 s / 100 mL, comparable to Examples 1 and 2, within a suitable range, demonstrating that the pore size optimization design of the gradient sandwich structure effectively balances air permeability and oil / moisture barrier properties. The antibacterial properties were particularly outstanding, with inhibition rates of 99.7% and 99.9% against Escherichia coli and Staphylococcus aureus, respectively, the highest among the three. This was attributed to the increased chitosan and citric acid concentrations in the barrier layer, which significantly enhanced the broad-spectrum antibacterial activity of the material by increasing the positive charge density and acidic environment.
[0080] Comparative Example 1: Based on Example 2, this example only modifies the gradient structure fabrication process; the remaining steps are the same as in Example 2. The specific settings are as follows:
[0081] The performance testing method for the comparative product is completely consistent with that of Example 1. Partial performance characterization was performed, and the characterization results are shown in the table below.
[0082]
[0083] Analysis of the above characterization results clearly demonstrates the necessity of the gradient three-layer structure design of this invention and the crucial role of the synergistic effect of each functional layer: Group D1-1 (oil-proof layer only): The number of oil-permeable paper stains is significantly higher than in Example 2, indicating the lack of support and synergistic barrier effect of the base layer and barrier layer; the oil-proof layer alone cannot effectively resist ink penetration. The wet strength is much lower than in Example 2, indicating that the inert support film cannot provide a high-strength hydrogen bond network similar to the microfibrillated cellulose base layer and its wet bonding force with the barrier layer. Although the air permeability is better than in Example 2, this "optimization" comes at the cost of sacrificing the biodegradability and mechanical strength of the material, and does not meet the core objective of biodegradability of this invention.
[0084] Group D1-2 (without barrier layer): The number of oil-permeable paper stains was 3.5 times that of Example 2, clearly indicating that the barrier layer (sodium alginate-chitosan composite layer) plays an indispensable role in preventing the penetration of oily substances, and its absence leads to a severe decline in barrier performance. The wet strength was lower than that of Example 2, indicating that the barrier layer, through its interaction with the substrate layer, makes a significant contribution to improving the mechanical stability of the material in high-humidity environments. The air permeability was significantly deteriorated, far worse than that of Example 2, indicating that the absence of the barrier layer disrupted the gradient pore structure design, resulting in a substantial reduction in air permeability.
[0085] Group D1-3 (homogeneous single-layer structure): This group performed the worst in all performance indicators. The number of oil-permeable paper stains reached as high as 9, 4.5 times that of Example 2, proving that mixing the three functional materials to form a homogeneous single layer completely eliminates the dense barrier network effect synergistically constructed by the layers in the gradient structure. The wet strength was also far lower than that of Example 2, indicating that the layered structure is beneficial for optimizing the bonding force within each layer and the interlayer interface bonding force, while homogenization destroys this advantageous structure. Air permeability deteriorated drastically, almost completely losing its permeability. This directly reflects that homogenization leads to a chaotic pore structure and unreasonable pore size distribution within the material, severely hindering gas passage and completely violating the design intent of this invention to maintain moderate air permeability while ensuring barrier performance.
[0086] The performance data from the three experimental groups in Comparative Example 1 powerfully demonstrate from the opposite perspective that the gradient sandwich structure design of "porous cellulose base layer + hydrophilic barrier layer + oleophobic and oil-repellent layer" adopted in this invention, along with the specific material composition and preparation process of each functional layer, is the key to achieving the material's excellent oil repellency, high wet strength, suitable air permeability, and complete biodegradability. Any simplification or substitution of the gradient structure or specific functional layers will lead to a significant decrease in material performance or even the loss of its core function.
[0087] Comparative Example 2: Based on Example 2, this example only modifies the preparation of the oil-resistant layer; the remaining steps are the same as in Example 2. The specific settings are as follows:
[0088] The performance testing method for the comparative product is completely consistent with that of Example 1. Partial performance characterization was performed, and the characterization results are shown in the table below.
[0089]
[0090] Analysis of the above characterization results shows that the type and characteristics of the oleophobic components in the oleophobic layer have a decisive influence on the material's oleophobic performance and environmental friendliness: Group D2-1 (using unmodified nano-silica): The number of oil-permeable paper stains was as high as 6, significantly worse than Example 2. The contact angle dropped to 95°, far lower than the 115° of Example 2. This indicates that the surface of the unmodified nano-silica particles is highly hydrophilic, making it difficult to uniformly disperse in the zein ethanol solution and construct a dense oleophobic network structure, resulting in insufficient integrity of the oleophobic barrier and easy penetration of ink.
[0091] Group D2-2 (without modified nano-silica): The number of oil-permeable paper stains further increased to 7, and the contact angle was only 85°, exhibiting the worst oil-repellent performance. This clearly demonstrates that hydrophobic modified nano-silica acts as a key filler in the oil-repellent layer, and its surface hydrophobicity is a core element in achieving a high contact angle and low stain count. Without this component, the oil-repellent layer relies solely on the inherent oleophobicity of zein, failing to form an effective nano-reinforced composite oleophobic barrier. Notably, the degradation rate was slightly higher than in Example 2. This is attributed to the complete absence of inorganic nanoparticles in the system, theoretically making it more susceptible to microbial decomposition; however, the severe lack of oil-repellent performance renders this group unusable.
[0092] Group D2-3 (using food-grade paraffin as a substitute): Although the number of oil-permeable paper stains was better than D2-1 and D2-2, it was still significantly higher than Example 2. The contact angle indicates that paraffin can provide some oleophobicity, but the oil-repellent effect is still inferior to that of modified nano-silica. The degradation rate dropped sharply to 40.6%, and significant paraffin residue was present. This proves that petroleum-based paraffin has poor compatibility with bio-based systems (zein, microfibrillated cellulose substrate), making it difficult to achieve molecular-level dispersion; more importantly, the bioinertness of paraffin severely hinders the effective decomposition of it by microorganisms in the composting environment, resulting in the inability of the material to achieve complete biodegradation, which violates the core design goal of this invention.
[0093] Comparative Example 3: Based on Example 2, this example only modifies the oil-resistant coating material; the remaining steps are the same as in Example 2. The specific settings are as follows:
[0094] The performance testing method for the comparative product is completely consistent with that of Example 1. Partial performance characterization was performed, and the characterization results are shown in the table below.
[0095]
[0096] Analysis of the characterization results above reveals the fundamental shortcomings of traditional alternative materials in achieving a balance between oil resistance and environmental friendliness.
[0097] Group D3-1 (using PLA coating): The number of oil-permeable paper stains decreased to 1, better than the 2 in Example 2, indicating that the PLA coating, with its high molecular oleophobicity and uniform film-forming properties, can construct a denser physical barrier, effectively blocking ink penetration. However, the degradation rate dropped sharply to 38.2%, far lower than in Example 2. This is attributed to the continuous film structure formed by the PLA coating at a thickness of 10 μm, which hinders the microbial contact and degradation activity of the substrate layer. Furthermore, the degradation rate of PLA in the composting environment is significantly lower than the biocompatibility design of the oil-resistant layer (corn gliadin-nano silica composite system) of this invention, resulting in insufficient overall material degradation.
[0098] Group D3-2 (using PET coating): Zero oil-permeable paper stains were observed, achieving optimal oil-repellent effect. This demonstrates that the high oleophobicity and low surface energy of the PET coating can achieve near-perfect ink blocking. However, the degradation rate was completely lost, directly reflecting the nature of PET as a petroleum-based non-degradable plastic—its chemical inertness makes it almost undecomposed by microorganisms in a composting environment. Furthermore, the coating structure completely isolates the interaction between the base layer and the composting medium, thoroughly violating the core degradability objective of this invention.
[0099] The oil-resistant layer of this invention (based on zein, hydrophobically modified nano-silica and anthocyanin microcapsules) maintains a high degradation rate while ensuring excellent oil resistance through the synergy of nanocomposite and bio-based materials; while alternative materials such as PLA or PET can improve single properties, they do so at the expense of environmental friendliness and cannot meet the needs of comprehensive applications.
[0100] Comparative Example 4: Based on Example 2, this example only modifies the preparation of the barrier layer; the remaining steps are the same as in Example 2. The specific settings are as follows:
[0101] The performance testing method for the comparative product is completely consistent with that of Example 1. Partial performance characterization was performed, and the characterization results are shown in the table below.
[0102]
[0103] Analysis of the above characterization results showed that the number of oil-permeable paper stains in Comparative Example 4-1 reached 4, significantly higher than the 2 in Example 2. This indicates that the barrier layer's ink-blocking performance was significantly reduced after replacing the sodium alginate-chitosan composite system with sodium alginate alone. This is attributed to the insufficient positive charge density due to the lack of chitosan, which prevents effective adsorption and neutralization of oily substances. Simultaneously, the network structure formed by sodium alginate alone is loose and has increased porosity, reducing the density of the oil-resistant barrier. The wet strength retention rate was only 58.7%, far lower than in Example 2, indicating that chitosan enhances the wet stability of the barrier layer through ionic crosslinking with sodium alginate. Its absence weakens the interlayer bonding force and the overall hydrogen bond network strength, resulting in severe degradation of the material's mechanical properties under high humidity conditions. In this scheme, the sodium alginate-chitosan composite system is indispensable in the gradient structure of this invention. The two work synergistically to construct a highly efficient hydrophilic barrier layer, which can optimize oil-blocking performance and improve wet strength. Any attempt to simplify this composite system will disrupt the overall performance balance of the material.
Claims
1. A method for preparing biodegradable greaseproof paper, characterized in that, The method includes: 1) mixing nanocellulose, bagasse slurry and modified starch, and forming a porous substrate layer by wet papermaking; 2) spraying a sodium alginate-chitosan composite solution onto the surface of the substrate layer to form a hydrophilic barrier layer; 3) mixing anthocyanin microcapsules, zein and hydrophobically modified nanosilica as a coating material, coating it onto the surface of the barrier layer to form an oil-proof layer, and making a biodegradable oil-proof paper.
2. The method for preparing a biodegradable oil-proof paper according to claim 1, characterized in that, The nanocellulose in step 1) is microfibrillated cellulose with a fiber length of 1.2 to 1.5 mm, and its addition amount is 38 to 42% of the total mass of the mixed pulp; the bagasse pulp in step 1) is bleached bagasse pulp that has undergone delignification treatment; the modified starch in step 1) is hydroxypropylated cassava starch, and its addition amount is 8 to 12% of the total mass of the mixed pulp.
3. The method for preparing a biodegradable oil-proof paper according to claim 1 or 2, characterized in that, Step 1) The wet papermaking process is carried out at a water temperature of 43-47 ℃, a slurry concentration of 0.8-1.2 wt%, and a papermaking pressure of 0.1 MPa. The resulting substrate layer has a thickness of 0.12-0.15 mm and a porosity of 60-70%.
4. The method for preparing a biodegradable oil-proof paper according to claim 1, characterized in that, Step 2) The sodium alginate-chitosan composite solution consists of 2-3 wt% sodium alginate, 1.5-2.5 wt% chitosan, 0.5-1 wt% citric acid, and the remainder is distilled water.
5. A method for preparing a biodegradable oil-proof paper according to claim 1 or 4, characterized in that, Step 2) The spraying amount of the sodium alginate-chitosan composite solution is 6-10 g / m². 2 The substrate is uniformly sprayed with an air knife coating machine and dried with hot air at 38-42 ℃ for 30-50 s.
6. The method for preparing a biodegradable oil-resistant paper according to claim 1, characterized in that, Step 3) The anthocyanin microcapsules have a particle size of 50-80 μm and are added at 6-8% of the total mass of the coating material; Step 3) The zein is a zein ethanol solution with a zein content of 10-15 wt%; Step 3) The hydrophobically modified nano-silica has a particle size of 80-100 nm and is added at 15-20% of the total mass of the coating material.
7. A method for preparing a biodegradable oil-proof paper according to claim 1 or 6, characterized in that, Step 3) The anthocyanin microcapsules are prepared as follows: anthocyanin solution and wall material solution are prepared separately, and anthocyanin microcapsules are prepared by sharp-pore coagulation bath method.
8. A method for preparing a biodegradable oil-proof paper according to claim 1 or 6, characterized in that, Step 3) The modification method of the hydrophobic modified nano silica is as follows: Nano silica and octadecyltrimethoxysilane are mixed evenly at a mass ratio of 1:0.2 and reacted at an environment temperature of 75 ℃ for 2 h.
9. The method for preparing a biodegradable oil-resistant paper according to claim 1, characterized in that, Step 3) The coating process uses a microgravure coating method, and the coating amount is controlled at 5-7 g / m². 2 After coating, pre-curing is performed at 58–62 °C for 5–7 min, followed by curing at 79–81 °C for 2–4 min, resulting in an oil-resistant layer thickness of 0.03–0.05 mm.
10. A biodegradable oil-resistant paper prepared by any one of claims 1 to 9.